1994
DOI: 10.1177/026765919400900207
|View full text |Cite
|
Sign up to set email alerts
|

Haematocrit measurements during cardiopulmonary bypass surgery: comparison of three stat methods with a blood cell counter

Abstract: Monitoring packed cell volume (PCV) is essential to safeguard oxygen delivery to the tissues during cardiopulmonary bypass (CPB). We compared the results obtained using a PCV monitor, a blood gas analyser and a microcentrifuge with those from a laboratory-based automated blood cell counter. PCV was measured in 221 samples of 40 patients undergoing open-heart surgery. The limits of agreement (mean difference +/- 2 SD) was unacceptably wide when the results obtained with the PCV monitor and the blood gas analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In addition, it should be pointed out that the Sysmex, which measures hematocrit via a pulsometric method, is not a golden standard for hematocrit measurement. The micro-centrifugal method is commonly accepted for this, 18,19 although it should be noted that hemodilution may also alter the viscosity and volume of packed red cells. 20 Undoubtedly, the Sysmex will have some bias with respect to the golden standard, but the magnitude of the bias of the GEM in comparison with the Sysmex suggests that the GEM will still have a substantial bias with respect to microcentrifugal hematocrit.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be pointed out that the Sysmex, which measures hematocrit via a pulsometric method, is not a golden standard for hematocrit measurement. The micro-centrifugal method is commonly accepted for this, 18,19 although it should be noted that hemodilution may also alter the viscosity and volume of packed red cells. 20 Undoubtedly, the Sysmex will have some bias with respect to the golden standard, but the magnitude of the bias of the GEM in comparison with the Sysmex suggests that the GEM will still have a substantial bias with respect to microcentrifugal hematocrit.…”
Section: Discussionmentioning
confidence: 99%
“…As these dynamic changes are likely to occur during surgery or ICU, the conductivity‐based POCT results should be interpreted with caution in these circumstances (McMahon & Carpenter, ; Stott et al , ; McNulty et al , ; Hopfer et al , ; Stadlbauer et al , ). A downward bias has been demonstrated when the Hct is below 30% (al‐Odeh et al , ). In one study, for example, the use of arterial blood‐gas POCT (GEM Premier 3000) in patients undergoing cardio‐pulmonary bypass surgery could have resulted in over‐transfusion of more than two‐thirds of the 55 patients who had participated in the study (Steinfelder‐Visscher et al , ).…”
Section: Haemoglobin Poct In Hospital Settingsmentioning
confidence: 99%
“…It is reported that the accuracy of a continuous on-line monitor reads hematocrit between 3.7% lower and 6.2% higher than the standard blood cell counter method and always reads higher for diluted samples with the difference as high as 7.5%. 5 Laboratory studies indicate that hematocrit m easured by the ratio of two spectral intensities is affected by the blood oxygenation level. 6 The spectral intensities are also dependent upon temperature variations that occur during cardiac surgical procedures.…”
Section: Introductionmentioning
confidence: 99%